Effect of straight micro fins on heat transfer and pressure drop of R410A during evaporation in round tubes. (February 2018) - Yang, Cheng-Min; Hrnjak, Pega
Highlights: R410A flow boiling experiments were conducted in smooth and axil micro-finned tubes. Straight micro-fins effectively enhance HTC in round tubes. HTC enhancement factor ranges from 1.03 to 1.48, and the average is around 1.34. Pressure drop penalty factor ranges from 0.66 to 1.6, and the average is around 1.23. Partial dry-out in the axial micro-finned tube occurs at lower vapor quality. Abstract: The objective of this paper is to present the influence of straight micro-fins on heat transfer coefficient and pressure drop. R410A flow boiling experiments were conducted in both smooth tube and the axial micro-finned tube. Data are taken at 10 °C saturation temperature for the vapor quality from 0.1 to 0.9, mass flux from 100 to 450 kg/s-m 2, and heat flux from 10 to 20 kW/m 2 . The results in the smooth tube were compared with several correlations and used as a baseline. It was observed that straight micro-fin structure played an important role in the evaporative heat transfer. The heat transfer coefficient was significantly enhanced in the axial micro-finned tube, whose enhancement factor ranged from 1.03 to 1.48 with average of 1.34. As the mass flux and vapor quality was low, the straight micro-fins had stronger influence of the heat transfer coefficient since the liquid-phase refrigerant was easily trapped in the grooves of the axial micro-finned tube. The pressure drop penalty factor of the axial micro-finned tube ranged from 0.66 to 1.6, and the average was around 1.23.